Józefitki na Ukrainie - Jastrzębowska, Marta (Annales Missiologici Posnanienses, 2012)
Congregation of St. Joseph Sisters was founded at the end of century by Rev. Zygmunt Gorazdowski, today saint. This foundation took its place in Lwów. The central service of St. Joseph Sisters is propagation of the gospel of merciful love by the service to the poor, elder and lonely, as well as the care of the ill, children and young people. After the changes in Ukraine in the 1990's it is now possible for the sisters to come back to this country. Sisters from Poland try to come back to the society, where they started. In the Ukraine’s new reality, they are involved in the work of re-evangelization.